ANALISIS RASIO LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS PADA APOTEK LA’TAHZAN FARMA TANAH GROGOT - Mariatul Kiptia; Amir Hamzah; Syifi Fauziyah (Paser Institute Of Accounting and Finance, 2023)
La'Tahzan Farma Pharmacy Tanah Grogot is a limited liability company in retail trade for pharmaceutical goods. The result of this study is that the liquidity ratio analysis shows that the company is in fairly good condition in fulfilling its short-term obligations, with a current ratio of 4.6 in 2020, 12.1 in 2021, and 23.5 in 2022. The quick ratio in 2020 is 1.1; in 2021, it is 2.2; and in 2022, it is 5.1. The cash ratio in 2020 is 16%; in 2021, it will be 48%, and in 2022, it will be 94%. The solvency ratio analysis shows that the company, in fulfilling all of its debts, is in very good condition, as can be seen from the DAR (Debt to Asset Ratio) ratio in 2020 of 16%, 2021 of 6%, and in 2022 of 3%. DER (Debt to Equity Ratio) in 2020 will be 20%, in 2021, it will be 6%, and in 2022, it will be 3%. The profitability ratio analysis shows that the company is still not optimal in obtaining its profits, as seen from the gross profit margin ratio (Profit Margin) in 2020 of 22%, 2021 of 22%, and 2022 of 24%. The net profit margin (Net Profit Margin) in 2020 is 1%; in 2021, it is 1%; and in 2022, it is 1%. ROI (Return on Investment) in 2020 will be 6%; in 2021, it will be 5%; and in 2022, it will be 3%. ROE (Return on Equity) in 2020 was 7%; in 2021, 6%; and in 2022, it was 3%.